The Expanding Mycovirome of Aspergilli - Battersby, Josephine L; Stevens, David A; Coutts, Robert H A; Havlíček, Vladimír; Hsu, Joe L; Sass, Gabriele; Kotta-Loizou, Ioly (Journal of fungi (Basel, Switzerland), 2024)
Mycoviruses are viruses that infect fungi and are widespread across all major fungal taxa, exhibiting great biological diversity. Since their discovery in the 1960s, researchers have observed a myriad of fungal phenotypes altered due to mycoviral infection. In this review, we examine the nuanced world of mycoviruses in the context of the medically and agriculturally important fungal genus, Aspergillus. The advent of RNA sequencing has revealed a previous underestimate of viral prevalence in fungi, in particular linear single-stranded RNA viruses, and here we outline the diverse viral families known to date that contain mycoviruses infecting Aspergillus. Furthermore, we describe these novel mycoviruses, highlighting those with peculiar genome structures, such as a split RNA dependent RNA polymerase gene. Next, we delineate notable mycovirus-mediated phenotypes in Aspergillus, in particular reporting on observations of mycoviruses that affect their fungal host's virulence and explore how this may relate to virus-mediated decreased stress tolerance. Furthermore, mycovirus effects on microbial competition and antifungal resistance are discussed. The factors that influence the manifestation of these phenotypes, such as temperature, fungal life stage, and infection with multiple viruses, among others, are also evaluated. In addition, we attempt to elucidate the molecular mechanisms that underpin these phenotypes, examining how mycoviruses can be targets, triggers, and even suppressors of RNA silencing and how this can affect fungal gene expression and phenotypes. Finally, we highlight the potential therapeutic applications of mycoviruses and how, in an approach analogous to bacteriophage therapy, their ability to produce hypovirulence in Aspergillus might be used to attenuate invasive aspergillosis infections in humans.
Keywords: phage therapy; Aspergillus; antifungal treatment; mycotoxins; mycovirus-host interactions; Polymycovirus; oxidative stress; RNA silencing; Pseudomonas aeruginosa; hypovirulence; RNA sequencing; mycovirus; aspergillosis